Toxicant Disruption of Immune Defenses: Potential Implications for Fetal Membranes and Pregnancy - Harris, Sean M.; Boldenow, Erica; Domino, Steven E.; Loch-Caruso, Rita (Frontiers in Physiology, 2020)
In addition to providing a physical compartment for gestation, the fetal membranes (FM) are an active immunological barrier that provides defense against pathogenic microorganisms that ascend the gravid reproductive tract. Pathogenic infection of the gestational tissues (FM and placenta) is a leading known cause of preterm birth (PTB). Some environmental toxicants decrease the capacity for organisms to mount an immune defense against pathogens. For example, the immunosuppressive effects of the widespread environmental contaminant trichloroethylene (TCE) are documented for lung infection with Streptococcus zooepidemicus. Group B Streptococcus (GBS; Streptococcus agalactiae) is a bacterial pathogen that is frequently found in the female reproductive tract and can colonize the FM in pregnant women. Work in our laboratory has demonstrated that a bioactive TCE metabolite, S-(1, 2-dichlorovinyl)-L-cysteine (DCVC), potently inhibits innate immune responses to GBS in human FM in culture. Despite these provocative findings, little is known about how DCVC and other toxicants modify the risk for pathogenic infection of FM. Infection of the gestational tissues (FM and placenta) is a leading known cause of PTB, therefore toxicant compromise of FM ability to fight off infectious microorganisms could significantly contribute to PTB risk. This Perspective provides the current status of understanding of toxicant-pathogen interactions in FM, highlighting knowledge gaps, challenges, and opportunities for research that can advance protections for maternal and fetal health.